KINERJA DINAS KOMUNIKASI DAN INFORMATIKA KOTA PONTANAK DALAM PELAYANAN INFORMASI BERBASIS ELEKTRONIK JEPIN (JENDELA PONTIANAK INTEGRASI) - Ismail Ismail; Nur Laili Azizah (Jurnal Media Birokrasi, 2021)
Jendela Pontianak Integrasi (JEPIN) is an electronic-based public information service system that is a product of the Pontianak City Communication and Informatics Office. JEPIN aims to be a forum for information about the needs of the community, the Pontianak city government, and community complaints. This research is based on the findings of obstacles experienced by the agency in the application of the system through secondary data. The purpose of this research is to find out the performance of the Pontianak City Communication and Informatics Office in organizing JEPIN information services. This research is qualitative descriptive research with inductive approach (from special to general) Interview, observation and documentation data collection techniques. Data analysis techniques used include data reduction, data presentation and conclusion drawing. The results of research at the Department of Communication and Informatics Pontianak city showed that the performance of the office in electronic-based information services is still not running well, this is seen from 5 (five) dimensions of the assessment of the performance of the office which 4 (four) of them did not meet the target that has been determined. Namely productivity, quality of service, responsiveness, and responsiveness, only the dimension of accountability meets the targeted service. Keyword: Jendela Pontianak Integrasi (JEPIN), Performance, Information Services